Forage Productivity, Quality and Soil Nutrients Status of Guinea Grass (Panicum maximum Jacq.) based Pasture as Influenced by Legumes Intercropping and Weed Control - Ram, S N (Annals of Arid Zone, 2017)
An experiment was conducted during 2007-2011 under rainfed conditions on sandy loam soil at Central Research Farm of Indian Grassland and Fodder Research Institute, Jhansi to study the effect of legumes intercropping and weed control on forage productivity, quality and soil nutrients status of Guinea grass based pasture in semi-arid conditions. The treatment comprised four legumes (Stylosanthes hamata, S. seabrana, Clitoria ternatea and Macroptillium atropurpureum) and four weed management practices (weedy check, hand weeding, weeding with weeder cum mulcher and pre-emergence application of pendimethalin @ 0.75 kg a.i. ha-1). Intercropping of Stylosanthes seabrana with Guinea grass produced significantly higher total dry forage yields (6.68 t ha-1) than Clitoria ternatea (5.41 t ha-1), Macroptillium atropurpureum (5.60 t ha-1) and S. hamata (6.29 t ha-1). Intercropping of S. seabrana with Guinea grass also recorded significantly higher total crude protein yield (582.0 kg ha-1) as compared to C. ternatea (457.7 kg ha-1) and M. atropurpureum (474.9 kg ha-1). In weed management practices, hand weeding 35 days after sowing in 1st year and 25 days after onset of monsoon rain from 2nd year onwards recorded significantly higher dry forage and crude protein yields of both Guinea grass (5.02 t ha-1 and 344.0 kg ha-1) and legumes (2.0 t ha-1 and 271.8 kg ha-1) than weedy check, pre-emergence application of pendimethalin @ 0.75 kg a.i. ha-1 and weeding with weeder cum mulcher. The intercropping of S. seabrana with Guinea grass recorded significant improvement in organic carbon (0.48%) and available nitrogen (228 kg ha-1) than C. ternatea and M. atropurpureum. Available nitrogen (226.2 kg ha-1), phosphorus (9.91 kg ha-1) and potash (195.8 kg ha-1) were also increased significantly in hand weeding plots than weedy check (211.3, 9.05 and 179.1 kg ha-1).